Design and implementation of a simple electromechanical system to reduce domestic gas wastage and accidents in South-Asia - M. Huq, Rachaen; Hoque, Md. Anamul; Chakraborty, Partha; B. Jafar, Imran; Rahman, Khan H. (© 2012 IEEE, 2016)
This conference paper was presented in the 6th International Conference on Sensing Technology, ICST 2012; Kolkata; India; 18 December 2012 through 21 December 2012 [© 2012 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/ICSensT.2012.6461750